Peculiarities of Innovative Technologies in Developing Cognitive Activity - Baydullayeva Firuza Akilbekovna (Researchparks Publishing, 2022)
The article deals with the issues based on analyzing peculiarities of innovative technologies in developing cognitive activity. It is known that, pedagogy, like any other science, is subject to numerous changes and development. This is primarily due to the fact that society has more and more new requirements for specialists. Innovative technologies help pedagogy find more efficient, effective ways to transform an ordinary person into a socially significant person. Innovative technologies have become a consequence of constant development, improvement of methods, i.e. technologies, thanks to which there is an integrative process of new ideas in education. However, the introduction of such technologies is associated with a number of difficulties (financial resources, the conservatism of some teachers in the educational field, insufficient development of technologies).